Self-medication Practice and Associated Factors among Private Health Sciences Students in Gondar Town, North West Ethiopia. A Cross-sectional Study - Zemene Demelash Kifle MSc; Abebe Basazn Mekuria MSc; Demssie Ayalew Anteneh MSc; Engidaw Fentahun Enyew MSc (SAGE Publishing, 2021)
Self-medication is the most common practice worldwide and it may lead to irrational use of drugs. Therefore, this study aimed to assess the prevalence of self-medication practice and its associated factors among health science students. A cross-sectional study was conducted on 600 health science students in Gondar town. The data regarding self-medication practice and its associated factors were collected using a face-to-face interview on a structured questionnaire. SPSS −24 was used for data analysis and explained with univariate, and multivariate logistic regression analysis to determine the factors associated with self-medication practice (sex, age, religion, marital status, residence, department, year of study, monthly income, access to pharmacy, and peer/family pressure). A total of 554 students responded to the questionnaire with a response rate of 92.3%. Out of 554 respondents, 78.2% were practiced self-medication. Headache/fever 37.88% (n = 164) was reported as the most common complaint to practice self-medication. Among the reasons for self-medication practice, similarity of symptoms with past illness 33.49% (n = 145) was the most frequently reported. In current study, Females (AOR = 3.11, 95% CI = 1.55, 6.25), Muslim followers (AOR = 2.78, 95% CI = 1.30, 5.91), Protestant followers (AOR = 4.25, 95% CI = 1.38, 13.07), pharmacy students (AOR = 3.72, 95% CI = 1.97, 9.30), clinical nursing students (AOR = 2.88, 95% CI = 1.87, 14.48), monthly income (>500ETB) (AOR = 2.49, 95% CI = 1.12, 5.56), distance of health institution (<30 min) (AOR = 2.79, 95% CI = 1.39, 5.61), and accessibility of pharmacy (AOR = 4.85, 95% CI = 2.08, 11.29) were the independent predictors of self-medication practice. Self-medication is common in health science students in Gondar town. Health professionals should educate students on the risks and benefits of self-medication to encourage responsible self-medication. National guidelines on medicine access should be developed and strong measures should be implemented to halt the selling of medications without a proper prescription.